Implications of climate change on the reproductive success of the Southern Yellow-billed Hornbill, Tockus leucomelas - Van de Ven, Tanja M F N (Percy FitzPatrick Institute of African Ornithology, 2018)
The effects of environmental warming on the reproductive performance of birds are most easily studied in desert habitats where birds already experience air temperatures (Tₐs) close to their upper thermal tolerance. Many desert birds coincide breeding with periods of food availability triggered by rainfall during the summer season. Daily maximum air temperatures (ₘₐₓ) during the Kalahari summer season frequently reach the lower forties (°C) and recent years have been characterised by reduced rainfall and increased Tₐ. Breeding Southern Yellow-billed Hornbills (Tockus leucomelas) could be particularly vulnerable to high Tₐ due to their breeding strategy whereby the females are confined to the nest cavity for most of the nesting period. During this time their male partners are solely responsible for food provisioning, which imposes a considerable energetic demand. In this thesis, I investigated the extent to which Tₐ affects the ability and willingness of breeding males to provision their female partners and offspring. And consequently, the extent to which male investment and the thermal environment affect female body mass (Mb) and chick development rates in Southern Yellowbilled Hornbills in the Kalahari. During three consecutive hornbill breeding seasons (October - March, between 2012 and 2015), I collected life history data during 50 breeding attempts by 32 hornbill pairs. At the study site, Southern Yellow-billed Hornbills readily breed in artificial nest boxes and this allowed me to assess the internal nest climate using temperature and relative humidity loggers which were placed in most of the nests. The male hornbills in the study population were semi-habituated which facilitated behavioural observations. Weather data were recorded at an on-site weather station. Morphometric data from females and chicks were collected on a daily basis at selected nests and perch scales installed at nest entrances recorded Mb data of the provisioning males. From chick hatching to chick fledging, I observed the behaviour of the males during 30-min focal follows and focussed on foraging behaviour, prey allocation decisions (nest versus self), microsite use and thermoregulatory behaviour. Male hornbills spent more than half of their time panting at Tₐs above 34.5 °C. Days on which this threshold temperature was exceeded were therefore described as 'hot days'. The male hornbills experienced trade-offs on hot days between foraging efficiency and panting behaviour, indicating that the additional cost of thermoregulation and high Tₐ affected foraging success (Chapter 2). Males would always provision larger prey items to the nest and consumed the smaller prey items themselves. As Tₐ increased, the males increased their foraging effort, but caught fewer and smaller prey items overall, reducing the total biomass they provisioned to the nest as well as the biomass they consumed. As a result, males were unable to maintain their Mb on days when Tₐ exceeded 37.9 °C (Chapter 3). A similar effect of hot days on Mb maintenance was observed in females and chicks within the nest. Independent of chick age, females departed the nest when their Mb reached a lower limit of 189.3 ± SD 18.1 g. The females would then aid the males in nest provisioning, however the negative effect of increasing ₘₐₓ on provisioning rate was still evident; i.e. females were not able to compensate for reduced male provisioning rates on hot days. High Tₐs during the nesting period resulted in smaller and lighter fledglings and overall reduced the probability of a successful nesting attempt (Chapter 4). A thermal imaging experiment revealed that the large beak of hornbills (both males and females) plays an important role in non-evaporative heat loss. Hornbills were observed to dissipate up to 19.9 % of the total non-evaporative body heat loss via the beak. This water-saving mechanism can be highly advantageous to hornbills living in arid regions where water availability is limited (Chapter 5). Lastly, a comparison of the results of the current study with those of a study on the same hornbill population carried out between 2008 and 2011 revealed that mean ₘₐₓ as well as rainfall during the nesting period had an important impact on overall hornbill reproductive effort and success (Chapter 6). Long-lived species are expected to prioritise future reproductive opportunities over current broods. However, the predicted scenario for the Kalahari is that high Tₐs become more extreme and periods of drought become more frequent. Therefore, I predict an increased risk of breeding failure among Southern Yellow-billed Hornbills in the future which could affect the persistence of this population.